Canned longganisa rice - Regalario, Roxanne C.; Azanza, Ma. Patricia V. (2001., 2001)
ABSTRACT the study was undertaken to establish a thermal process for canned longganisa rice. Phase I dealt with the selection of the most acceptable commercial formulation of the local sausage. A 30 panel sensory evaluation indicated that the most acceptable formulation was CDO Smoked Pork Longganisa. This selected formulation was described as moderately sweet and slightly salty and spicy with a moderately strong aroma and flavor. The color of the longganisa was reddish brown with firm and slightly compact but tender texture. Phase II of the study indicated that the most suitable cultivar for canned longganisa rice was Irrigated Rice (IR42). This cultivar has high anylose content and is low gelatinization temperature type rice. The established optimum longganisa to rice ratio was 20:80. The thermal process for canned longganisa rice was established in Phase III based on Ball's mathematical method. The rice-processing steps used ere washing , hydration, pre-gelatinization, and addition of emulsion. Results indicated the use of acidified rice prevented excessive gelling if canned rice. Results of the Sensory Evaluation showed that the longganisa rice product was acceptable and had characteristics longganisa aroma and flavor. The rice was described as very reddish brown and slightly tough. Validation of the calculated thermal process must be done.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Canned food; Convenience food